Adubação do Eucalyptus urophylla S.T. Blake em solo arenizado no bioma Pampa - Souza, Huan Pablo de (2017)
Eucalyptus is the most planted forest genus in Brazil and in the world. Populations are established in the most varied environments and provide different levels of productivity. In the state of Rio Grande do Sul, new plantations are being established in the region of the Pampa biome, where there are sanded soils due to natural processes or even accelerated through anthropic activity. These soils have low natural fertility. At present, the management used presents unsatisfactory results from a productive and economic point of view. In this context the present work intends to contribute with viable alternatives to the use of the sanded soils for the forest production with species of the genus Eucalyptus. The objective of this work was to evaluate the silvicultural aspects of Eucalyptus urophylla submitted to five fertilization regimes, with three replications for each treatment. The experiment was carried out in May 2015 in a sandstone core in the municipality of Maçambará - RS, owned by the company StoraEnso Florestal, totaling 27.000 m² of experimental area in the form of a completely randomized design (DIC). The number of seedlings was the same for all treatments, since the sources and doses of fertilizers were varied according to the expected biomass production. Monthly litter production and incident rainfall were determined, at 12 and 24 months determined the biomass production and yield of the treatments. At 12 months, the highest height was reached for the T5 treatment, with 4.20 meters and 3.89 cm of DAP. The highest biomass production at 12 months was for T 5, with 6.82 Mg ha-1, followed by T 4 with 5.88 Mg ha-1, then T 2 with 5.12 Mg ha-1, T 3 with 4.83 Mg ha-1 and with the lowest biomass production the T 1 with 4.35 Mg ha-1. At 24 months, the highest productivity was observed for the T 5 with 28.20 m³ ha-1 year-1, which represents 58.12% more than the T 1, which presented 11.80 m³ ha-1 year-1. The highest litter production, between 12 and 24 months, was observed for the T5 with 1406.58 kg ha-1year-1, which represents 61.29% more than the litter produced in T 1, which was 544.54 kg ha-1year-1. The mean annual rainfall was 1922 mm, which corresponds between August 2015 and May 2017. The element that presented the lowest mean concentration in the precipitation solution was P, with 0.01 mg L-1 , the highest concentrations were observed for N and Ca with 1.08 g L-1. The highest precipitated amount was found for the Cl with 7.46 kg ha-1year-1, followed by Ca with 7.02 kg ha-1year-1. The lowest amount was observed for P with 0.06 kg ha-1year-1. N was the element that presented the highest concentration in the biomass at 12 months, being more concentrated in the leaves. Mn was the micronutrient with higher concentrations at 12 months, also for leaves in all treatments. At 12 months K was the element with the highest accumulation in biomass with 51.68 kg ha-1 in the T 5 treatment and 26.97 kg ha-1 in T 1. The Mn was the micronutrient with the highest accumulation at 12 months, with 5792.67 g ha-1 in the T 5 treatment. At 24 months, the highest concentrations in the biomass were observed for Ca in the treatments T 1, T 3, T 4 and T 5, mainly in the bark already in T 2 the highest concentration was N in the leaves. Mn is the micronutrient with the highest concentrations at 24 months, mainly in the bark component. The highest accumulated amounts of macro nutrients at 24 months were observed for Ca in treatments T 1, T 3, T 4 and T 5, while T 2 obtained a higher accumulation of K. The results obtained in this work are expected to contribute with alternatives for the use of degraded sandy soils through the implantation of forest stands. Throughout the rotations we believe in the improvement of the chemical and physical characteristics of the soil, through the cycling of nutrients and biological activity, besides the protection offered by the trees in the ground cover.